Women Entrepreneurs Problems in Pakistan (A Study of District Mardan) - Ismail Shahid; Luis Antonio Bittar Venturi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The aim of this study is to discover different problems faced by women entrepreneurs in district Mardan Pakistan. For this research 40 questionnaires were distributed among the respondent using a simple random sampling method to collect information about women entrepreneurs who work in different areas of district Mardan. The results are presented in the form of a pie chart, Bar Graph and interpreted using the simple average method. Like most developing countries, women entrepreneurs in Pakistan and Mardan face particular gender discrimination and suffer from scarcity and poor access to resources. The lack of information about the product market, education and training, assistant to government agencies, etc., without the encouragement of male family members, and inadequate network mechanisms are other problems faced by women entrepreneurs.